2017
DOI: 10.3390/ijms18112401
|View full text |Cite
|
Sign up to set email alerts
|

Spirulina maxima Extract Ameliorates Learning and Memory Impairments via Inhibiting GSK-3β Phosphorylation Induced by Intracerebroventricular Injection of Amyloid-β 1–42 in Mice

Abstract: Spirulina maxima, a microalga containing high levels of protein and many polyphenols, including chlorophyll a and C-phycocyanin, has antioxidant and anti-inflammatory therapeutic effects. However, the mechanisms where by Spirulina maxima ameliorates cognitive disorders induced by amyloid-β 1–42 (Aβ1–42) are not fully understood. In this study, we investigated whether a 70% ethanol extract of Spirulina maxima (SM70EE) ameliorated cognitive impairments induced by an intracerebroventricular injection of Aβ1–42 in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 45 publications
0
21
0
Order By: Relevance
“…The antioxidant compounds in spirulina, such as phycobilins and phycocyanins, also inhibit the activities of catalytic enzymes, such as lipoxygenase and cyclooxygenase, or enhance the activity of enzymes, such as glutathione peroxidase, catalase, and superoxide dismutase [59,60]. These polyphenols were reported to have anti-inflammatory, antiviral, antioxidant, antithrombotic, vasodilatory, antidiabetic, neuroprotective, hepatoprotective, and anticarcinogenic properties [21,22,24,28,29,32,[35][36][37][59][60][61][62][63]. However, the metabolic pathways for the formation of phenolic compounds in spirulina and their importance are still unknown [64].…”
Section: Discussionmentioning
confidence: 99%
“…The antioxidant compounds in spirulina, such as phycobilins and phycocyanins, also inhibit the activities of catalytic enzymes, such as lipoxygenase and cyclooxygenase, or enhance the activity of enzymes, such as glutathione peroxidase, catalase, and superoxide dismutase [59,60]. These polyphenols were reported to have anti-inflammatory, antiviral, antioxidant, antithrombotic, vasodilatory, antidiabetic, neuroprotective, hepatoprotective, and anticarcinogenic properties [21,22,24,28,29,32,[35][36][37][59][60][61][62][63]. However, the metabolic pathways for the formation of phenolic compounds in spirulina and their importance are still unknown [64].…”
Section: Discussionmentioning
confidence: 99%
“…ese findings indicated that Spirulina maxima extract ameliorated cognitive impairment through the inhibition of Aβ accumulation and acetylcholinesterase activity. Spirulina maxima extract also suppressed hippocampal oxidative stress of Aβ (1-42)-induced mice through enhancing the antioxidant system in the glutathione metabolism pathway by increasing the GSH level and attenuating the decrease of glutathione peroxidase and glutathione reductase protein expression levels [227]. is suggested that the inhibition of Aβ accumulation and acetylcholinesterase activity by Spirulina maxima extract could contribute to the suppression of oxidative stress.…”
Section: Marine Macroalgae (Seaweeds)mentioning
confidence: 92%
“…Another cyanobacterium, Spirulina maxima, belonging to the Oscillatoriaceae family, has been known to have many physiologically active substances such as carotenoids, chlorophylls, polysaccharides, vitamins, and C-phycocyanin [225,226]. In mouse model of Alzheimer's disease induced by Aβ , Spirulina maxima extract ameliorated learning and memory impairments in Aβ (1-42)-induced mice (assessed using the passive avoidance and Morris water maze tests), decreased the protein expression levels of hippocampal Aβ (1-42), amyloid precursor protein (APP), and β-site APP cleaving enzyme 1 (BACE1) and attenuated the increase in acetylcholinesterase activity in the hippocampal oxidative stress of Aβ (1-42)-induced mice [227]. ese findings indicated that Spirulina maxima extract ameliorated cognitive impairment through the inhibition of Aβ accumulation and acetylcholinesterase activity.…”
Section: Marine Macroalgae (Seaweeds)mentioning
confidence: 99%
See 1 more Smart Citation
“…Amyloid‐β (Aβ) is considered as one of the major pathological mediators in the pathogenesis of Alzheimer's disease (AD) and abnormal accumulation of Aβ impair synaptic function and induces cognitive deficits. The development of cognitive deficits of Alzheimer's type in animals is very successfully done by an intracerebroventricular injection (ICV) of Aβ 1‐42, which delivers the peptide in the ventricles of the brain [24,25]. Accordingly, a single ICV injection of Aβ 1‐42 (100 µ m /10 µL) was employed to induce symptoms of Alzheimer's disease in mice as per previously reported studies [26].…”
Section: Methodsmentioning
confidence: 99%